On the Role of Projected FDI Inflows in Shaping Institutions: The Longer-Term Plan for Post-Pandemic Investment Reboot - Xiang Gao; Zhenhua Gu; Kees Koedijk (East Asian Economic Review (EAER), 2020)
Capital inflows have a strong presence that influences destination countries' development of institutions, which can in turn help resuscitate a stopped economy and re-attract capital that was lost during crises such as the recent public health crisis. While the previous literature emphasizes the mechanism that foreign investors press or even threaten the local government for change, this paper explores empirically whether institutional improvement can be achieved through the channel that host countries voluntarily reform institutions in anticipation of potential investments predicted by the exogenous geographical and cultural characteristics of the recipient countries. Given that countries with better institutional quality can accumulate larger FDI stocks, we still find that the need for more FDI, in contrast to FPI and debt, gives higher incentives to host countries to strategically improve their institutions before seeking capital overseas. Moreover, the predicted FDI exerts more prominent impacts on institutions on constraining elite than those involved in launching a business, enforcing contracts, and protecting properties. The results imply that a long-run plan for upgrading elite constraint institutions is crucial for a post-pandemic FDI reboot.
Keywords: E02; F21; F34; F40; P48; 330; Foreign Direct Investment; Foreign Portfolio Investment; Debt Investment; Legal Institutions; Contract Enforcement; Executive Constraints; Property Rights